1991
DOI: 10.1007/bf00776711
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial tumors of the first year of life

Abstract: The introduction of new diagnostic tools for neuroimaging has resulted in the early recognition of congenital brain tumors. In the present report the authors describe an International Multicenter Series of 886 children with brain tumor, in whom the diagnosis was obtained during the first 12 months of life. Most of the tumors were located within the supratentorial compartment. In spite of a relatively high operative mortality, surgery still appears to be the more effective therapy. Radiotherapy in this age grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 0 publications
7
29
0
Order By: Relevance
“…This could reflect a real increase in incidence or could be related to change in diagnostic procedures [4,5,6]. As previously reported by many authors [7,8,9,10,11,12], males seem to be more susceptible than females. The male to female ratio in our series was 1:1.2, just like in other published reports.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This could reflect a real increase in incidence or could be related to change in diagnostic procedures [4,5,6]. As previously reported by many authors [7,8,9,10,11,12], males seem to be more susceptible than females. The male to female ratio in our series was 1:1.2, just like in other published reports.…”
Section: Discussionsupporting
confidence: 51%
“…Astrocytomas were reported as the most common CNS tumors of childhood by some authors [7, 9, 10, 11, 13]. In our patient population, medulloblastoma was somehow the most common tumor (27.5%), closely followed by astrocytoma (25.8%) and craniopharyngioma (14.1%).…”
Section: Discussionmentioning
confidence: 81%
“…In the literature 1–5 % of pediatric brain tumors are plexus papillomas [1, 2, 7, 8]. Several studies have shown that the majority of these tumors occurred in the first 2 years of life [5, 6]. This was confirmed by the extensive analysis of brain tumor incidence in children by Jänisch [3], who identified choroid plexus papilloma as the most common intracranial tumor in infants with an incidence of up to 24%.…”
Section: Discussionsupporting
confidence: 50%
“…While they comprise less than 1% of all intracranial tumors in the general population [1, 2], they are one of the most common intracranial tumors in infants [3, 4]. The preferred localization of the choroid plexus papilloma is the lateral ventricle in children and the fourth ventricle in adults [5,6,7,8]. The clinical symptoms are not only caused by the space-occupying effect of the lesion and disturbed cerebrospinal fluid (CSF) circulation, but also by increased CSF synthesis as a result of hypersecretory hydrocephalus [9].…”
Section: Introductionmentioning
confidence: 99%
“…These tumors are classically distributed with a posterior fossa preponderance. However, in clinical practice, more than 50% of pediatric tumors of the central nervous system are supratentorial [3, 4]. …”
Section: Discussionmentioning
confidence: 99%